Ophthalmic Pathology in the Offspring of Pregnant Women with Gestational Diabetes Mellitus. - Alvarez-Bulnes, Olga; Monés-Llivina, Anna; Cavero-Roig, Lluís; Ventura, Paula Sol; Llagostera-Benedico, Josefina; Valls-Sirera, Carme; Talló-Catarineu, Gemma (Maternal & Child Health Journal, 2020)
Background: Gestational diabetes (GD) occurs in 5.8% to 25.1% of pregnant women. This disorder has been linked with intrauterine growth delays, congenital anomalies, and neurobehavioral disorders following birth. As to ophthalmological effects, changes in macular thickness and hypoplasia of the upper quadrant of the papilla have been described. Objective: To investigate whether GD has an effect on ophthalmological development in the children born of mothers with this condition. Methods: Observational study carried out in children seen in the ophthalmological outpatient clinic of a pediatric hospital in Barcelona (Spain) between January 2011 and December 2015. Participants were ultimately divided into two groups, a study group whose mothers had GD managed either by insulin or diet (GD group) and a control group of children with non-diabetic mothers. Pregestational diabetes cases, were excluded. Complete information was collected on the children's refraction status, ophthalmological disease, and congenital malformations. Results: Data were compiled on 350 children (229 children born of mothers with GD-186 managed with diet vs 43, with insulin- and 121 controls). The prevalence of amblyopia and strabismus was similar between the groups, but children of mothers with GD had a three-fold greater probability of having refractive errors than children born to mothers without GD. Hyperopia (14.8% vs. 7.4%) and myopia (3.5% vs 0%) were found to be significantly more prevalent in children born of mothers with GD than in the controls (p = 0.027 in both groups).The prevalence of astigmatism was similar in both groups (1.7% vs 0.8%). Conclusions for Practice: Refractive errors are more common in children born of mothers with GD. These conditions are easily managed, but if they are not detected, they can lead to amblyopia or accommodative strabismus, interfere with acquisition of fine motor skills, and lead to learning problems. Regular ocular examinations would be recommended in these patients.